2007
DOI: 10.1111/j.1472-765x.2007.02189.x
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A-producing Aspergilli in Vietnamese green coffee beans

Abstract: Aims:  To determine the incidence and severity of infection by ochratoxin A (OA)‐producing fungi in Vietnamese green coffee beans. Methods and Results:  Aspergillus carbonarius, A. niger and yellow Aspergilli (A. ochraceus and related species in section Circumdati) were isolated by direct plating of surface‐disinfected Robusta (65 samples) and Arabica (11 samples) coffee beans from southern and central Vietnam. Significantly, more Robusta than Arabica beans were infected by fungi. Aspergillus niger infected 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 21 publications
3
32
0
3
Order By: Relevance
“…A. niger was also effective. In a study of Leong et al (2007), none of the tested isolates of A. niger produced OTA. Schuster et al (2002) stated that only 3-10% of A. niger strains examined for OTA production were toxinogenic under favourable conditions.…”
Section: Ochratoxin a Detoxification And Inhibition Of Ochratoxin A Amentioning
confidence: 94%
“…A. niger was also effective. In a study of Leong et al (2007), none of the tested isolates of A. niger produced OTA. Schuster et al (2002) stated that only 3-10% of A. niger strains examined for OTA production were toxinogenic under favourable conditions.…”
Section: Ochratoxin a Detoxification And Inhibition Of Ochratoxin A Amentioning
confidence: 94%
“…In Brazil, the presence of OTA in coffee beans has been vigorously evaluated with contamination levels varying significantly [94,[110][111][112][113]. OTA has been identified in coffee from various countries around the World, such as Australia [114], France [115,116], India [17], Netherlands [117], Saudi Arabia [118], Switzerland [119,120], and USA [121].…”
Section: Occurrence Of Ota In Coffeementioning
confidence: 99%
“…Since the first detection of OTA in green coffee by Levi et al, 1974) other studies have confirmed the presence of this mycotoxin in various coffee-based products, such as roasted coffee and instant coffee (Leoni et al, 2000). OTA has been identified in manufactured coffee from various countries, such as Vietnam (Leong et al, 2007), France (NARI, 2004), India (Gopinandhan et al, 2008), the Netherlands (Van der Stegen et al, 2001), and the Czech Republic (Malir et al, 2014). The reported average Pittet et al (1996) (1.1 µg/kg) and of Prado et al (2000) (1.7 µg/kg).…”
Section: Resultsmentioning
confidence: 96%